Psammomatous Thoracic spinal meningioma with osseous metaplasia: A very rare case report (Bangladesh Journal of Neurosurgery, 2020)
Thoracic spinal psammomatous meningioma is a rare subtype of meningioma. Amongdiverse types of mesenchymal differentiation, osseous metaplasia is found to be stillrarer. We are presenting a new case of thoracic psammomatous spinal meningiomawith osseous metaplasia in a middle aged female which that gives a sense of cancellousbone in the spinal canal. To conclude, meningiomas with osseous metaplasia are veryrare tumors that complicate the surgical removal in certain cases. Ossification, ifpredicted prior to operation with computed tomography reconstruction, makes planningof removal easier. In our case, maintained cerebrospinal fluid spaces despite firmconsistency of tumor made its removal easier once cerebrospinal fluid was drained.We have submitted this article because it is very rare and curable pathology andpreoperative diagnosis helps in prevention of neurological injury during its excisionBang. J Neurosurgery 2020; 9(2): 142-145